A comparative study between dynamic shake table test and shear box test in a centrifuge. Issue 2 (June 2009) - Shibayama, S.; Izawa, J.; Takahashi, A.; Yamada, T.; Nagatani, H.; Ohbo, N.; Kusakabe, O.
Abstract : A comparative study of centrifuge dynamic shake table test and centrifuge pseudo-static shear box test was conducted on the same prototype model to experimentally examine applicability of the seismic displacement method which is adopted in seismic design for underground structures in Japan. The model used was a rectangular shape tunnel embedded in dry sand. The detailed strain measurements were made on the model tunnels as well as relative displacement between upper and lower slabs of the tunnel for direct comparison between the results obtained from the two different test types. The study confirmed that the centrifuge pseudo-static shear box test provides valuable information on structural responses which are very much similar to those observed in the centrifuge shake table test.